A new innovation paradigm: combining technological and social innovation - Kohlgrüber, Michael; Schröder, Antonius; Bayón Yusta, Félix; Arteaga Ayarza, Asier (Technische Universität Dortmund, 2019)
A new innovation paradigm is needed to answer the societal, economic and environmental challenges the world and companies are facing. The EU funded Horizon 2020 SPIRE Project “Coordinating Optimisation of Complex Industrial Processes” (COCOP) is combining technological and social innovation within a steel company pilot case (Sidenor). The project aims at reducing raw materials consumption (and energy and emissions reduction as well) by plant-wide optimisation of production processes based on a software solution and at the same time changing social practices. Key for COCOP is a methodology integrating technological innovation within a social innovation process of co-creation and co-development by involving (potential) users of the future software system and relevant stakeholders right from the beginning; thereby improving effectiveness and impact of the innovations and the implementation process. This involvement is instructed and measured by social key performance indicators (social KPIs) and operationalised in surveys (questionnaire and interviews) with future users, engineers and external experts (from different industry sectors not involved in the project). The article presents the results of the starting point of COCOP illustrating the future user perspective of the pilot steel company (Sidenor) contrasted by the view of external experts – seriously taking into account the interfaces between technology, human and organisation.
Un nouveau paradigme d’innovation : combiner innovation technologique et innovation sociale
Matériaux & techniques;107(1)
Keywords: Social innovation; Plant-wide optimisation; Co-creation; Human factor requirements; 300